1995
DOI: 10.1002/app.1995.070560305
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented impact testing of castor‐oil‐based polyurethanes

Abstract: SYNOPSISInstrumented impact testing has been used to study castor-oil-based polyurethanes. The energy-absorbed capacity of these materials in impact is dependent on several factors, such as the type of isocyanate, NCO/OH ratio, and testing temperature. An approximate but simple method for the low-temperature impact testing was proposed. A change from ductile response to brittle fracture was observed as the temperature of the specimen was reduced. This characteristic ductile-brittle transition temperature is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…19 Data on the total impact energy of graft IPNs are reported together with those of tensile toughness in Figure 8. In contrast to the tensile toughness, the total impact energies are below the values calculated from the additive law, except those corresponding to a narrow composition window of 25-30% PU, where the total im- pact energy is a little higher than the calculated value.…”
Section: Toughness and Impact Energymentioning
confidence: 99%
See 1 more Smart Citation
“…19 Data on the total impact energy of graft IPNs are reported together with those of tensile toughness in Figure 8. In contrast to the tensile toughness, the total impact energies are below the values calculated from the additive law, except those corresponding to a narrow composition window of 25-30% PU, where the total im- pact energy is a little higher than the calculated value.…”
Section: Toughness and Impact Energymentioning
confidence: 99%
“…[12][13][14][15][16][17][18] In our previous work, 19,20 PUs prepared from castor oil showed high impact properties and a large synergistic effect in the mechanical properties of IPNs obtained from methyl methacrylate and castor oil. In this work, IPNs were prepared from epoxy resin and castor oil following a sequential method of synthesis, and their morphology and thermal and mechanical properties were determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, vegetable oils have become attractive for the synthesis of PUDs because of their economical benefits and the fact that they are made from renewable resources [18][19][20][21][22][23]. CO is one of the vegetable oils that used as polyol in the synthesis of PU due to its cheapness and availability as renewable material [24][25][26]. It is a triglyceride of fatty acids with ricinoleic acid being the major constituent (about 90 %).…”
Section: Introductionmentioning
confidence: 99%
“…Already, several polymers have demonstrated their qualities that would be well suited for such an application [7][8][9][10][11][12]. However, if the concerns about corrosion could be brushed aside for copper, this metal has many outstanding properties which justify that its consideration be maintained as a candidate material for the fabrication of the container walls.…”
Section: Introductionmentioning
confidence: 99%
“…A literature research has revealed many valuable works performed on the physico-mechanical properties of castor oil-based polyurethanes; and the effects of chain extenders, isocyanate structure, and hard-to-soft ratio [13][14][15][16]. However, no research has been performed on the study of the radiation effects on natural castor oil-based polyurethanes.…”
Section: Introductionmentioning
confidence: 99%